Pendistribusian Kartu Indonesia Pintar (KIP) - Ratna Indah Cahyaningsih (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
The Indonesia Pintar Program (PIP) is an enhanced support program for the government for Poor Student Assistance (BSM). The PIP program is expected to help students who are economically disadvantaged and can ease the burden of disadvantaged families, and withdraw students who drop out of school due to delinquent fees. So it is hoped that there will be no more reason not to continue their education to a higher level because of cost problems. For the use of funds to be used as effectively and efficiently as possible. Thus the PIP program can support the government's 12-year compulsory education program. Both programs can go hand in hand with the Indonesian national goal of Educating the Nation's Life.